Kali Linux wireless penetration testing : beginner's guide : master wireless testing techniques to survey and attack wireless networks with Kali Linux, including the KRACK attack /: beginner's guide : master wireless testing techniques to survey and attack wireless networks with Kali Linux, including the KRACK attack. (2017) - Buchanan, Cameron; Ramachandran, Vivek
No abstract available